Electrocatalytic Performances of Carbon Supported Metallophthalocyanine and Pt/Metallophthalocyanine Catalysts Towards Dioxygen Reduction in Acidic Medium - ÖZKAYA, ALİ RIZA (SPRINGER, 2009)
Electrocatalytic performances of phthalocyanines (Pcs) involving N-benzyl-4-phenyloxyacetamide moieties, dispersed on a high-surface area carbon substrate, Vulcan XC-72 (VC) and Nafion (Nf), towards oxygen reduction in acidic medium were determined and compared. The VC/Nf/CoPc(5) catalyst showed much higher catalytic activity than those of the other Pc(1-4)-based catalysts (H2Pc 1, ZnPc 2, NiPc 3 and CuPc 4) and that of unsubstituted CoPc-based one. The comparison of the performance of VC/Nf/Pt-5 dual catalyst with that of VC/Nf/Pt one indicated that the former can be a good alternative to the latter as a cathode catalyst both in direct methanol and H-2/O-2 fuel cell applications.
Keywords: Phthalocyanines; Platinum; Oxygen reduction; Electrocatalysis; Methanol tolerant catalyst; METAL TETRASULFONATED PHTHALOCYANINES; HIGH-AREA CARBON; OXYGEN-REDUCTION; HYDROGEN-PEROXIDE; COBALT PHTHALOCYANINES; O-2 REDUCTION; ELECTROREDUCTION; METHANOL; ELECTROLYTE; STABILITY